Pengaruh Sistem Pengendalian Internal dan Kualitas Sistem Informasi Akuntansi terhadap Akurasi Perhitungan Biaya Produksi pada PT.Tunggal Mitra Plantation-PKS Manggala Kabupaten Rokan Hilir - Mukhazza Albitha Alsha; Yenni Samri Juliati Nasution; Muhammad Syabudi (Jurnal Riset Akuntansi, 2026)
This study aims to examine the influence of internal control systems and the quality of accounting information systems on the accuracy of production cost calculations at PT. Tunggal Mitra Plantation – PKS Manggala. Accurate production cost calculation is essential for improving operational efficiency, supporting managerial decision-making, and ensuring reliable financial reporting. This research employs a quantitative approach using a survey method. The population consists of employees involved in accounting, finance, and production activities, with 31 respondents selected through the total sampling technique. Data were collected using structured questionnaires and analyzed using multiple linear regression with SPSS software. The findings indicate that the internal control system has a significant positive effect on the accuracy of production cost calculations. Likewise, the quality of the accounting information system significantly enhances the accuracy of cost determination. Simultaneously, both variables demonstrate a significant influence on production cost accuracy, indicating that effective internal controls supported by reliable accounting information systems contribute to more precise and consistent cost calculations. The coefficient of determination (Adjusted R Square) of 0.810 shows that 81% of the variation in production cost accuracy is explained by these two variables, while the remaining 19% is influenced by other factors not examined in this study. These findings highlight the importance of strengthening internal control mechanisms and improving accounting information system integration to enhance operational performance, cost management, and strategic decision-making.